2021
DOI: 10.4314/ahs.v21i4.12
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles in highly active antiretroviral treatment non-adherent, adherent and naive HIV-1 infected patients in Western Kenya

Abstract: Background: Cytokines play an important role in signaling the immune system to build an adequate immune responseagainst HIV. HIV distorts the balance between pro and anti-inflammatory cytokines causing viral replication. Highly active antiretroviral treatment (HAART) acts by trying to restore pro and anti-inflammatory cytokine balance. It is not clear how HAART non-adherence influences circulating cytokine levels. This study therefore determined cytokine levels in HAART non-adherent individuals. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(43 reference statements)
2
3
1
Order By: Relevance
“…Inflammatory cytokines such as IL-12 and IFNg as well as the inflammation-related cytokines IL-6 and IL-1b were lowly expressed among viral failure adolescents, while the expression of inflammatory cytokine CCL3 was higher among those experiencing virological failure. In fact the low level of IFNg observed in a context of sub-optimal virological response was similar to what have been observed in studies conducted in Brazil and Kenya where a low concentration of IFNg was observed in adolescents with a detectable viral load (31) and ART non-adherent people living HIV with active viral replication (32). Even though there was not significance association between TNFa and viral load, we have noticed a low level of this inflammation cytokine in adolescents with virological suppression, similarly to what observed in a USA children cohort where low levels of TNFa correlated with low levels of viral load (33).…”
Section: Discussionsupporting
confidence: 86%
“…Inflammatory cytokines such as IL-12 and IFNg as well as the inflammation-related cytokines IL-6 and IL-1b were lowly expressed among viral failure adolescents, while the expression of inflammatory cytokine CCL3 was higher among those experiencing virological failure. In fact the low level of IFNg observed in a context of sub-optimal virological response was similar to what have been observed in studies conducted in Brazil and Kenya where a low concentration of IFNg was observed in adolescents with a detectable viral load (31) and ART non-adherent people living HIV with active viral replication (32). Even though there was not significance association between TNFa and viral load, we have noticed a low level of this inflammation cytokine in adolescents with virological suppression, similarly to what observed in a USA children cohort where low levels of TNFa correlated with low levels of viral load (33).…”
Section: Discussionsupporting
confidence: 86%
“…Of note, we observed several analytes which had significant correlations with duration of known infection in the cART group, including CCL11 (R = 0.53, p = 0.0166), granulocyte macrophage colony-stimulating factor (GM-CSF) (R = -0.46, p = 0.0403), IL-1α (R = -0.49, p = 0.0277), and IL-4 (R = -0.45, p = 0.0447). These findings are not entirely unexpected due to previous reports often showing pathologically lower levels of some cytokines in treated PWH compared to untreated PWH [22].…”
Section: Analyte Correlationssupporting
confidence: 81%
“…The observed low level of plasma IFN-γ could be explained by ART that blocking viral replication which would inhibit the synthesis of mRNA responsible for the production of IFN-γ as reported in Kenya [12]. However, other authors have reported elevated IFN-γ levels in HIV-1 infected patients as reported in USA [51,52].…”
Section: Discussionmentioning
confidence: 82%
“…While some studies have established a negative correlation between CD4 + T cells, IL-2, IFN-γ lymphocytes and plasma viral load in PLHIV-1 on ART [11], other studies have shown that high plasma levels of IL-4 and IL-10 were correlated with a high plasma viral load concomitant with low levels of CD4 + T cells [12]. Study have highlighted the effect of plasma viral load on the extent of cytokine disruption showing that when cytokines were less affected, plasma viral load remained lowered in PLHIV-1 on antiretroviral therapy [13].…”
Section: Introductionmentioning
confidence: 99%